Trajectories of Empire : Transhispanic Reflections on the African Diaspora - Branche, Jerome (Book collections on Project MUSE., 2022)
"A multi-disciplinary conversation about the origin and outcome of the modern black diaspora in its Iberian and Latin American dimensions"--